Koreksi Multiple Diastema Disertai Koreksi Kebiasaan Buruk Tongue Thrusting Menggunakan Alat Ortodonti Lepasan Kombinasi Tongue Crib - Putri Prihandayani; Reni Kurniasari (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2026)
Multiple diastema is a space or gap between two or more adjacent teeth. Diastema management can be corrected using removable orthodontic treatment and eliminating etiological factors. Treatment in this case shows the progress of successful treatment of multiple diastema in Soelastri General Hospital using removable orthodontic appliances based on the indications and needs of patient care. Case management: A 24-year-old woman came to Soelastri General Hospital Surakarta with complaints of gaps in the teeth between the 4 lower front incisors. The patient's bad habit history is known to be tongue thrusting. Intraoral examination found interdental gaps in the 4 lower incisors measuring 33.32 (1.6mm), 32.31 (1.2mm), 31.41 (1.1mm), 41.42 (1.3mm). Diastema closure with finger spring activation towards the mesial and labial arches of the upper and lower jaws. Activation was carried out gradually at each control so that the diastema at the fourth control on teeth 33-32 (0.5 mm). Conclusion: This shows that removable orthodontic appliances are effective for closing multiple diastema with mild to moderate degrees, with patient compliance in using the appliance and the effect of using a tongue crib in reducing the patient's tongue thrusting habit.